H3PO3 electrochemical behaviour on a bulk Pt electrode: adsorption and oxidation kinetics. (10th September 2016) - Prokop, M.; Bystron, T.; Paidar, M.; Bouzek, K.
Graphical abstract: Highlights: H3 PO3 competes for the adsorption sites with electrolyte anion and UPD hydrogen. Maximum H3 PO3 adsorption on Pt electrode observed at potential of zero charge. H3 PO3 oxidation on metallic Pt proceeds via electrochemical oxidation. H3 PO3 oxidation on PtOx surface takes place via reaction with surface Pt oxides. H4 P2 O6 is not intermediate of H3 PO3 oxidation at a Pt surface in H2 SO4 solution. Abstract: Polybenzimidazole-type polymer doped with H3 PO4 is commonly used as the proton-conductive phase in high-temperature proton-exchange membrane fuel cells. However, H3 PO4 is not stable during fuel cell operation and undergoes reduction by hydrogen on a Pt surface to phosphorus compounds in a lower oxidation state, such as H3 PO3 . In this work the kinetics of H3 PO3 oxidation on Pt electrode was studied, including an investigation of H4 P2 O6 as a possible oxidation intermediate. H3 PO3 adsorption in hydrogen underpotential deposition region was described by a triple Langmuir isotherm corresponding to adsorption on specific Pt crystalline planes. Co-adsorption of hydrogen as well as SO4 2−, HSO4 − ions decreased the total amount of adsorbed H3 PO3 . The determined apparent charge transfer coefficients of H3 PO3 anodic oxidation on a metallic Pt surface were found to be concentration and temperature-dependent, indicating that the nature of the anodic process is complex. From chronopotentiometric measurements of H3 PO3 and H4 P2 O6 oxidation on a preoxidised Pt surface it was concluded that, while H3 PO3 is oxidised by means of a chemical reaction with PtOx, H4 P2 O6 undegoes anodic oxidation on the PtOx surface. According to voltammetry and bulk electrolysis experiments H4 P2 O6 is not formed as an intermediate product during electrochemical oxidation of H3 PO3 on a metallic Pt surface.